Coherent Seismic Arrivals in the P Wave Coda of the 2012 Mw 7.2 Sumatra Earthquake: Water Reverberations or an Early Aftershock?. Issue 4 (25th April 2018) - Fan, Wenyuan; Shearer, Peter M.
Abstract: Teleseismic records of the 2012  M w  7.2 Sumatra earthquake contain prominent phases in the P wave train, arriving about 50 to 100 s after the direct P arrival. Azimuthal variations in these arrivals, together with back‐projection analysis, led Fan and Shearer (2016a, https://doi.org/10.1002/2016GL067785 ) to conclude that they originated from early aftershock(s), located ∼150 km northeast of the mainshock and landward of the trench. However, recently, Yue et al. (2017, https://doi.org/10.1002/2017GL073254 ) argued that the anomalous arrivals are more likely water reverberations from the mainshock, based mostly on empirical Green's function analysis of a M 6 earthquake near the mainshock and a water phase synthetic test. Here we present detailed back‐projection and waveform analyses of three M 6 earthquakes within 100 km of the M w  7.2 earthquake, including the empirical Green's function event analyzed in Yue et al. (2017, https://doi.org/10.1002/2017GL073254 ). In addition, we examine the waveforms of three M 5.5 reverse‐faulting earthquakes close to the inferred early aftershock location in Fan and Shearer (2016a, https://doi.org/10.1002/2016GL067785 ). These results suggest that the reverberatory character of the anomalous arrivals in the mainshock coda is consistent with water reverberations, but the origin of this energy is more likely an early aftershock rather than delayed and displaced water reverberations from the mainshock. Key Points: Anomalous coherent seismic arrivals are present in the teleseismic P wave train of the 2012 M w 7.2 Sumatra earthquake Waveform analysis of smaller earthquakes near the mainshock can be used to discriminate between source and path effects The observational evidence suggests that the mainshock likely triggered an early aftershock that generated strong water reverberations